Cover Picture: RevErbα Preferentially Deforms DNA by Induced Fit (ChemBioChem 5/2014). Issue 5 (21st March 2014) - Chung, Ying‐Hua; van der Vaart, Arjan
<x xml:space="preserve">Abstract</x> The cover picture shows binding of the RevErbα DNA‐binding domains to DNA. Although in the complex only minor distortions to DNA are observed, free‐energy simulations show that DNA deformation preferentially occurs by induced fit rather than by conformational selection. The simulations indicate that the presence of multiple apo‐state structures might not be sufficient to distinguish between binding models, and that information on the sequence of binding events is needed as well. For further information, see the communication by A. van der Vaart and Y.‐H. Chung on p. 643 ff. The image was produced by Aleksandra Karolak.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>